Construction of a human body model for acupuncture and moxibustion treatment by colored Petri nets. (December 2021) - Gan, Quan; Wu, Ren; Nakata, Mitsuru; Ge, Qi-Wei
Abstract: Acupuncture and moxibustion treatment has been widely spread all over the world because it has few side effects and is effective for ahead sick and incurable disease. However, the treatment is often performed empirically and clinically, and the mechanism and process of the treatment are not yet scientifically elucidated. Therefore, it is required to establish objective and unified research methods and evaluation criteria that incorporate modern Western medicine and scientific and technological viewpoints. In this paper, a human body model is constructed, which includes the internal organs and the meridians for acupuncture and moxibustion treatment based on traditional Chinese medicine using colored Petri nets. This model aims at expressing the relationship between acupoints and internal organs realistically and accurately in acupuncture and moxibustion treatment, and leading to realization of an objective analysis method of the mechanism and process of acupuncture and moxibustion treatment. Firstly, the calculation of the acupoints' efficacy on internal organs is discussed, and measurement equations and model construction methods are proposed. Next, an interface is established as a bridge to connect the internal organs and the meridians with acupoints. By Java language, a simulation system is developed based on the proposed Petri net model. Finally, simulations of acupuncture and moxibustion treatment are performed to verify the validity of model.